Post-Disaster Relocation of Urban Coastal Communities in the Philippines - Ginbert Permejo Cuaton (Department of International Relations, Universitas Andalas, 2019)
This paper examines the super typhoon Haiyan disaster as a case study that demonstrates the full complexity of multidimensional challenges, vulnerabilities, and adaptation needs of urban coastal communities at high risk of future impacts. Anchored on the Coastal Relocation Potential framework developed by Bukvic, Smith, and Zhang (2015), this qualitative research gathered data using a combination of desk research and field works in three urban coastal villages of Tacloban City highly devastated by Haiyan. Results showed that residents in urban coastal communities consider the following factors in deciding to relocate or not: a) household level socio-economic factors, b) psychosocial and physical impacts, c) post-disaster recovery concerns, and d) relocation assistance support needs. The study argues that policy-makers need proper planning, participatory consultation and great consideration to the socio-economic impacts it will cause to coastal dwellers, majority of which is urban-poor families.